Switching for Power: How Code-Switching Shapes Pakistani Political Talk Shows - Aqsa Batool; Dr. Hafiz Ahmad Bilal; Dr. Ijaz Asghar; Dr. Naveed Nawaz Ahmad (ACADEMIA International Journal for Social Sciences, 2025)
Codeswitching refers to the act of changing between two or more languages or dialects in a conversation and is a common characteristic of multilingual societies, Pakistan is no exception. In the Pakistani talk shows, code-switching has various communicative and social purposes including the linguistic diversity, cultural identity, and social hierarchies of the viewers and the speakers. This paper will examine the different uses of code-switching in televised talk shows and the theme addressed in signaling group membership, asserting solidarity or authority, making points, clarifying meaning, and controlling interpersonal relationships. The chosen talk shows, in Urdu and English media, were used to gather data and apply the qualitative discourse analysis to investigate code switching cases and their contextual meaning. The results indicate that hosts and guests often alternate languages in a strategic way to entertain the audience, bargain courtesy, establish social identity, and meet various needs of different audience groups. Also, code-switching is used as one of the stylistic devices to make the rhetorical effect, humor, or emotional outburst more effective. The study highlights the relevance of sociolinguistic value of code switching in media discourse which reflects the larger cultural, social, and pragmatic aspects in language choice. The insights are part of the interpretation of multilingual communication strategies in Pakistani media and their contribution to the creation of the discourse of people.